Breast Cancer. A Characterization in the Decade from 1996-2005. - Lidia Torres Ajá; Julio César Sarmiento Sánchez; Arístides Sánchez Sánchez; Otto Pacheco Ruiz; Nancy Capin Sarría; Práxedes Rojas Quintana (Medisur, 2007)
Background: Breast Cancer constitutes a health problem in Cuba due to it is the first cause and localization of death for malignant tumors in females. This situation has been considered by our health Minister as a number one priority of investigation. Objective: To characterize the behavior of breast cancer from the clinical-pathological point of view in Cienfuegos Province during 10 years. Method: An observational descriptive and prospective study of 100 per cent of the surgical operated patients with this entity in the Cienfuegos province during 10 years (from January 1996 to December 2005). Some variable such as sex, age, affected breast, topographic localization, histological variant, clinical stage at the time of diagnosing, modality of the used biopsy, surgical techniques applied, and municipality where the patient lives. Results: The incidence rate in some years is high in regard to the national scope. There is predominance in patients older than 50 years old as there is predominance in the infiltrantive duct carcinoma taking into consideration the histological type. Conclusions: Breast cancer constitutes a real health problem in our province with incidence rates which are increasing, as well as a great detection of cases in groups who were not considered at risk.